2021
DOI: 10.3389/fcell.2021.632779
|View full text |Cite
|
Sign up to set email alerts
|

Isoalantolactone Increases the Sensitivity of Prostate Cancer Cells to Cisplatin Treatment by Inducing Oxidative Stress

Abstract: Prostate cancer is the most common malignancy among men worldwide. Platinum (II)-based chemotherapy has been used to treat a number of malignancies including prostate cancer. However, the potential of cisplatin for treating prostate cancer is restricted owing to its limited efficacy and toxic side effects. Combination therapies have been proposed to increase the efficacy and reduce the toxic side effects. In the present study, we investigated how isoalantolactone (IATL), a sesquiterpene lactone extracted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Among the bioactive ingredients isolated from Inula helenium L, IATL has been demonstrated to possess considerable biological activities, including anticancer properties ( Chun et al, 2018 ; Yan et al, 2020 ). Studies have also found that IATL has no overt toxicity on mice ( Lu et al, 2018 ; Huang et al, 2021 ), suggesting that IATL is safe for consumption. Despite its potential cytotoxicity against a variety of cancer cells, no study on the anti-CRC effects of IATL has been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the bioactive ingredients isolated from Inula helenium L, IATL has been demonstrated to possess considerable biological activities, including anticancer properties ( Chun et al, 2018 ; Yan et al, 2020 ). Studies have also found that IATL has no overt toxicity on mice ( Lu et al, 2018 ; Huang et al, 2021 ), suggesting that IATL is safe for consumption. Despite its potential cytotoxicity against a variety of cancer cells, no study on the anti-CRC effects of IATL has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…They are often used either as drug leads or as actual drugs. Isoalantolactone (IATL) is a sesquiterpene lactone naturally occurring in the roots of Inula helenium L. IATL has been reported to exert cytotoxic effects against a variety of cancer cells, including pancreatic cancer ( Zhang et al, 2021 ), esophageal cancer ( Lu et al, 2018 ; Wen et al, 2018 ), hepatocellular carcinoma ( Kim et al, 2021 ), prostate cancer ( Rasul et al, 2013 ; Chen et al, 2018 ; Huang et al, 2021 ) and glioblastoma ( Xing et al, 2019 ). The anticancer effects of IATL mainly involve the induction of apoptosis, cell cycle arrest and autophagy ( Weng et al, 2016 ; Chen et al, 2018 ; Lu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not the first-line drug for prostate cancer chemotherapy [ 40 ], the development of cisplatin offers new hope for the treatment of prostate cancer [ 41 ]. Clinically, the application of cisplatin is limited because of its inherent and acquired drug resistance to prostate tumor cells, and other toxic and side effects [ 42 ]. In the experiments of Shanta Dhar et al [ 43 ], the hydrophobic Pt (IV) compound 1 was used as a prodrug for delivering cisplatin to prostate cancer by PSMA-targeted PLGA-b-PEG-NPs, which were made of poly(D,L-lactic-co-glycolic acid)-b-poly(ethylene glycol) (PLGA-b-PEG) nanoparticles (NPs).…”
Section: Aptamer–drug Delivery Systems Against Prostate Cancermentioning
confidence: 99%
“…We next set out to test if BdS could extend olaparib usage by other mechanisms. For example, ATL, a sesquiterpene lactone reminiscent in structure to IJ-5 and BdS (Figure 1C), can increase ROS levels in a number of transformed cell lines, which could explain the increased BdS sensitivity of Kuramochi cells given their pre-existing replication stress vulnerability (Figure 2C) [14,[38][39][40][41]. Importantly, the increased ROS levels induced by ATL can lead to oxidative DNA damage, marked particularly by the formation of the DNA base oxidation product 8-oxo-7,8-dihydroguanine (8-OxoG), which triggers the induction of base excision repair (BER) [14].…”
Section: Bds Synergises With Olaparib To Induce Dna Damage In P53 Wildtype Cancer Cellsmentioning
confidence: 99%